Cover Image, Volume 6, Issue 2. (March 2016) - Nakano, Masayoshi; Champagne, Benoît
Abstract : The cover image, by Masayoshi Nakano and Benoît Champagne, is based on the Overview Nonlinear optical properties in open‐shell molecular systems, DOI:10.1002/wcms.1242 . Abstract : The cover image, by Masayoshi Nakano and Benoît Champagne, is based on the Overview Nonlinear optical properties in open‐shell molecular systems, DOI:10.1002/wcms.1242 .